A New Numerical Nuclear Reactor Neutronics Code SHARK - Zhao, Chen; Peng, Xingjie; Zhang, Hongbo; Zhao, Wenbo; Chen, Zhang; Rao, Junjie; Liu, Kun; Gong, Zhaohu; Zeng, Wei; Li, Qing (Frontiers in Energy Research, 2021)
In order to establish the next-generation reactor physics calculation method based on the numerical nuclear reactor technology and realize high-fidelity modeling and calculation, a new numerical nuclear reactor neutronics code SHARK is developed. The code is based on the direct transport method with construct solid geometry (CSG) method, advanced subgroup resonance method, direct transport MOC method in rectangle and hexagonal geometry, large-scale parallel and odCMFD acceleration method. The macro hexagonal assembly case, VERA-2 and VERA-3 benchmarks are applied for the validation. Numerical results show good accuracy of SHARK and the direct transport method can be adopted on numerical nuclear reactor calculation.